2011
DOI: 10.1074/jbc.m111.234534
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Synthesis and Methylation of Phosphatidylethanolamine Promote Lipid Droplet Biosynthesis and Stability in Tissue Culture and in Vivo

Abstract: Triacylglycerols are stored in eukaryotic cells within lipid droplets (LD).The LD core is enwrapped by a phospholipid monolayer with phosphatidylcholine (PC), the major phospholipid, and phosphatidylethanolamine (PE), a minor component. We demonstrate that the onset of LD formation is characterized by a change in cellular PC, PE, and phosphatidylserine (PS). With induction of differentiation of 3T3-L1 fibroblasts into adipocytes, the cellular PC/PE ratio decreased concomitant with LD formation, with the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 69 publications
4
96
0
1
Order By: Relevance
“…Since phospholipids form the boundary between the aqueous environment of the cytoplasm and the interior neutral lipid core, their importance in maintaining lipid droplet structure is clear. Recently, phospholipid remodeling of PC (residing in the ER) to PS and later PE was shown to incorporate into the lipid droplet monolayer (39). Moreover, the enzyme PEMT was able to convert the remodeled PE into PC, suggesting that this enzyme plays an important role in lipid droplet biogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since phospholipids form the boundary between the aqueous environment of the cytoplasm and the interior neutral lipid core, their importance in maintaining lipid droplet structure is clear. Recently, phospholipid remodeling of PC (residing in the ER) to PS and later PE was shown to incorporate into the lipid droplet monolayer (39). Moreover, the enzyme PEMT was able to convert the remodeled PE into PC, suggesting that this enzyme plays an important role in lipid droplet biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As with most membranes, the major phospholipid found in the lipid droplet monolayer was PC with lower levels of PE, PS, PI, and SM also present. A lack of SM, PS, and PA in lipid droplets from Chinese hamster ovary (CHO) K2 cells was reported in another study (9) but subsequent work with other cell types and tissue including HepG2 cells (68), Niemann-Pick cells (45), alveolar macrophages (40), mammary tissue (38), and adipose tissue (39,54) record the presence of these lipids in isolated lipid droplet fractions. Since phospholipids form the boundary between the aqueous environment of the cytoplasm and the interior neutral lipid core, their importance in maintaining lipid droplet structure is clear.…”
Section: Discussionmentioning
confidence: 99%
“…PEMT localizes to the mitochondrialassociated ER membrane (MAM). In adipocytes, PEMT is found in close proximity to LDs and may use mitochondrial PE for the synthesis of PC on LDs [62]. How these two biosynthetic processes could be coupled remains unknown.…”
Section: Ld-mitochondria/peroxisome Interactionsmentioning
confidence: 99%
“…This substrate transfer may be assisted by membrane contact between mitochondria and the ER. A recent study has demonstrated that phosphatidylethanolamine synthesized by mitochondrial decarboxylation of phosphatidylserine is a substrate for methyltransferase reactions to form a significant portion of phosphatidylcholine coating LDs in adipocytes (24). Thus, some of the phospholipids on LDs are derived from mitochondrial synthesis.…”
Section: Lds Peroxisomes and Mitochondria Contribute To Neutral Lipmentioning
confidence: 99%
“…Phosphatidylethanolamine N-methyltransferase (PEMT) assembles methyl groups onto the ethanolamine headgroup to produce phosphatidylcholine. A recent study has shown that PEMT localizes to either LDs or ER or mitochondria-associated membranes closely associated with LDs in cultured adipocytes (24). Radiolabeled metabolites were used to demonstrate that PEMT contributes significantly to the phosphatidylcholine content of adipocyte LDs.…”
Section: Maturation Of Lds and Ld Fusionmentioning
confidence: 99%